A ruthenium, iridium, tin, and nickel mixed precious metal coating anode material and preparation method thereof

By forming a hybrid precious metal coating of ruthenium iridium tin nickel on the titanium anode material, combined with sandblasting and acid etching treatment, the problems of high cost, short life and poor stability of the titanium anode material are solved, and the electrode performance and stability are improved and the preparation process is simplified.

CN119776811APending Publication Date: 2025-04-08BAOJI ZHONGTITANIUM METAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411983858.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing titanium anode materials have high cost, short electrode life, poor stability, and complex preparation process, which is not conducive to the improvement of industrial production efficiency.

Method used

The titanium substrate is coated with a mixed metal salt solution of ruthenium, iridium, tin and nickel. The specific surface area of ​​the titanium substrate is increased by sandblasting and acid etching treatment, forming a ruthenium iridium tin nickel mixed precious metal coating, and adjusting the heat treatment conditions to improve electrode performance and stability.

Benefits of technology

It improves the electrochemical activity and stability of titanium anode materials, extends the service life of the electrode, simplifies the preparation process, reduces production costs, and improves industrial production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776811A_ABST
    Figure CN119776811A_ABST
Patent Text Reader

Abstract

The present invention provides a ruthenium, iridium, tin, and nickel mixed precious metal coating anode material and a preparation method thereof, and belongs to the technical field of titanium anode materials. The present invention sandblasts and acid-etches a titanium substrate, and then uses a mixed metal salt solution containing ruthenium, iridium, tin, and nickel for coating, heat treatment, and cooling to obtain a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material. The present invention adjusts the processing steps of the titanium substrate, and increases the specific surface area of ​​the titanium substrate by sandblasting and acid etching, thereby increasing the bonding strength and corrosion resistance between the coating and the titanium substrate. The present invention adjusts the raw materials and concentration of the mixed metal salt solution, improves the solvent environment, reduces the temperature of the heat treatment, and reduces the steps of the heat treatment, thereby improving the preparation efficiency, and the prepared anode material has high electrochemical activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium anode materials, and in particular to a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material and a preparation method thereof. Background Art

[0002] Titanium anode plate material is an insoluble anode material widely used in the electrochemical industry, also known as dimensionally stable anode, DSA (dimensionally stable anode). It is based on titanium metal and coated with an active coating with precious metal organic complexes or precious metal materials as the main components. It is a new type of high-efficiency electrode material developed in the late 1960s. Titanium anode was first used in the chlor-alkali industry and is now widely used in chemical industry, metallurgy, electroplating, water treatment, environmental protection, ocean, cathodic protection and other fields.

[0003] Since the titanium anode is coated with an active coating with precious metal organic complexes or precious metal materials as the main components, it has a high cost, so this type of anode material cannot be used in large quantities as a consumable. Even if precious metal anodes are used, the large amount of anode mud produced during the electrolysis process will cause a large amount of precious metal waste within the limited service life of the anode.

[0004] At present, precious metal coated titanium anodes have problems such as high cost, short electrode life, and poor stability. To solve the above problems, methods such as substrate replacement, substrate protection, and precious metal coating are usually used.

[0005] For example, Chinese patent 202410335311.7 discloses a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material and its preparation method, which forms a combined coating by coating a mixed metal salt solution of ruthenium, iridium, tin, and cobalt on a titanium substrate and then performing a step-by-step heat treatment, thereby improving the performance and stability of the electrode and extending the service life of the material. However, the preparation process requires repeated coating-heat treatment steps, and the preparation method is cumbersome, which is not conducive to improving the industrial production efficiency of titanium anodes.

[0006] Chinese patent 202110999012.X discloses a coated titanium anode for circulating cooling water treatment, a preparation method and an application, wherein an intermediate layer (TiC), a transition layer (TiO2-Co3O4-C) and a surface active layer (composed of TiO2, RuO2, IrO2, SnO2, CeO2, Co3O4 and C) are arranged on a titanium substrate. The titanium anode of this method reduces the loading of precious metals, effectively controls the electrode cost, and the oxygen-chlorine potential difference of the prepared titanium anode is greater than 200mV. Although the anode prepared by the above method improves the dechlorination efficiency and the effective chlorine content in the electrolyte during the electrolysis process to a certain extent, and also improves the service life of the electrode, its enhanced life is less than 140h.

[0007] Therefore, further developing a low-cost titanium anode material with good electrode performance and stability and long service life is the main problem to be solved at present. Summary of the invention

[0008] In view of this, the present invention provides a method for preparing a ruthenium, iridium, tin and nickel mixed precious metal coating anode material, by coating a mixed metal salt solution of ruthenium, iridium, tin and nickel on a titanium substrate, then subjecting the titanium substrate to thermal decomposition, cooling and then repeating the steps of coating, thermal decomposition and cooling to form a ruthenium, iridium, tin and nickel mixed coating on the surface of the titanium substrate, thereby improving the performance and stability of the electrode.

[0009] The method for preparing the ruthenium, iridium, tin and nickel mixed noble metal coating anode material of the present invention comprises the following steps:

[0010] (1) The titanium substrate is sandblasted and then acid treated to remove oxides, grease and other impurities on the surface of the substrate;

[0011] (2) immersing the treated titanium substrate in an acid solution for acid etching, then washing with water until neutral, and drying;

[0012] (3) preparing a mixed metal salt solution containing ruthenium, iridium, tin and nickel;

[0013] (4) uniformly coating the mixed metal salt solution on the acid-etched titanium substrate, heat-treating the coated titanium substrate, and then cooling it to room temperature, repeating the coating, heat-treating, and cooling steps 3-4 times to obtain a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material;

[0014] The heat treatment is to heat treat the coated titanium substrate at 100° C.-200° C. for 1 h-10 h under inert gas, and then heat treat it at 400° C.-600° C. for 20 min-240 min.

[0015] Preferably, the blasting material used in the blasting treatment in step (1) is steel shot or brown corundum.

[0016] Preferably, the acid treatment in step (1) is to immerse the titanium substrate after sandblasting in an aqueous solution of oxalic acid with a mass concentration of 15%-20% for 5-10 minutes.

[0017] Preferably, the acid solution in step (2) is a hydrochloric acid solution or an acetic acid solution with a mass concentration of 20-30%.

[0018] Preferably, the acid etching in step (2) is performed at a temperature of 75 to 85° C. and for a time of 10 to 30 minutes.

[0019] Preferably, the mixed metal salt solution in step (3) is a mixed solution of a soluble ruthenium salt, a soluble iridium salt, a soluble tin salt, and a soluble nickel salt; and the solvent of the mixed metal salt solution is any one or two of ethanol, ethylene glycol, n-butanol, or isopropanol.

[0020] Preferably, the soluble ruthenium salt is any one or more of ruthenium nitrate, ruthenium trichloride, ruthenium sulfate, and ruthenium acetate;

[0021] The soluble iridium salt is any one or more of iridium nitrate, iridium chloride and iridium sulfate;

[0022] The soluble tin salt is any one or more of tin tetrachloride, stannous chloride and tin sulfate;

[0023] The soluble nickel salt is any one or more of nickel acetate, nickel chloride, nickel sulfate and nickel nitrate.

[0024] Preferably, in the mixed metal salt solution, the concentration of ruthenium is 0.3-0.6 mg / mL; the concentration of iridium is 0.3-0.6 mg / mL; the concentration of tin is 0.3-1 mg / mL; and the content of nickel is 0.2-0.8 mg / mL.

[0025] The present invention also provides a ruthenium, iridium, tin and nickel mixed noble metal coating anode material prepared by the above method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention adopts a mixed metal salt solution of ruthenium, iridium, tin and nickel to coat a titanium substrate to form a mixed noble metal coating of ruthenium, iridium, tin and nickel. The obtained anode material has high electrochemical activity and stability.

[0028] The present invention adjusts the processing steps of the titanium substrate, increases the specific surface area of ​​the titanium substrate through sandblasting and acid etching, and further increases the bonding strength and corrosion resistance between the coating and the titanium substrate.

[0029] The invention adjusts the raw materials and concentration of the mixed metal salt solution, improves the solvent environment, reduces the temperature of the heat treatment, reduces the steps of the heat treatment, and improves the preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart of the preparation method of the ruthenium, iridium, tin and nickel mixed precious metal coating anode material. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a ruthenium, iridium, tin and nickel mixed noble metal coating anode material, the steps of which are as follows:

[0032] (1) The titanium substrate is sandblasted and then acid treated to remove oxides, grease and other impurities on the surface of the substrate;

[0033] (2) immersing the treated titanium substrate in an acid solution for acid etching, then washing with water until neutral, and drying;

[0034] (3) preparing a mixed metal salt solution containing ruthenium, iridium, tin and nickel;

[0035] (4) uniformly coating the mixed metal salt solution on the acid-etched titanium substrate, heat-treating the coated titanium substrate, and then cooling it to room temperature, repeating the coating, heat-treating, and cooling steps 3-4 times to obtain a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material;

[0036] The heat treatment is to heat treat the coated titanium substrate at 100° C.-200° C. for 1 h-10 h under inert gas, and then heat treat it at 400° C.-600° C. for 20 min-240 min.

[0037] In a specific embodiment of the present invention, the sandblasting material used in the sandblasting treatment in step (1) is steel shot or brown corundum, the diameter of the steel shot or brown corundum is 2-3 mm, the sandblasting is carried out under 0.5-1 MPa compressed air, 200 mm away from the sprayed substrate, the spray angle is about 20-30°, and it is sprayed at a high speed on the surface of the titanium substrate.

[0038] In a specific embodiment of the present invention, the acid treatment in step (1) is to immerse the titanium substrate after sandblasting in an oxalic acid aqueous solution with a mass concentration of 15%-20% for 5-10 minutes.

[0039] In a specific embodiment of the present invention, the acid solution in step (2) is a hydrochloric acid solution or an acetic acid solution with a mass concentration of 20-30%.

[0040] In a specific embodiment of the present invention, the acid etching in step (2) is performed at a temperature of 75 to 85° C. and for a time of 10 to 30 minutes.

[0041] In a specific embodiment of the present invention, the mixed metal salt solution in step (3) is a mixed solution of a soluble ruthenium salt, a soluble iridium salt, a soluble tin salt, and a soluble nickel salt; and the solvent of the mixed metal salt solution is any one or two of ethanol, ethylene glycol, n-butanol, or isopropanol.

[0042] In a specific embodiment of the present invention, the soluble ruthenium salt is any one or more of ruthenium nitrate, ruthenium trichloride, ruthenium sulfate, and ruthenium acetate;

[0043] The soluble iridium salt is any one or more of iridium nitrate, iridium chloride and iridium sulfate;

[0044] The soluble tin salt is any one or more of tin tetrachloride, stannous chloride and tin sulfate;

[0045] The soluble nickel salt is any one or more of nickel acetate, nickel chloride, nickel sulfate and nickel nitrate.

[0046] In a specific embodiment of the present invention, in the mixed metal salt solution, the concentration of ruthenium is 0.3-0.6 mg / mL; the concentration of iridium is 0.3-0.6 mg / mL; the concentration of tin is 0.3-1 mg / mL; and the concentration of nickel is 0.2-0.8 mg / mL.

[0047] The preparation method of the ruthenium, iridium, tin and nickel mixed noble metal coating anode material of the present invention is as follows: Figure 1 .

[0048] The present invention improves the surface morphology, structure and performance of the titanium substrate by sandblasting and acid etching, increases its surface roughness and specific surface area, and further improves its bonding strength and corrosion resistance with the coating. Sandblasting can make the surface of the substrate roughened initially, and the sand grain size and pressure of the sandblasting have an impact on the sandblasting result. The present invention adjusts the parameters of the sandblasting and combines with acid etching to obtain a titanium substrate with a rough surface.

[0049] The technical solution of the present invention is further described below in conjunction with embodiments.

[0050] Example 1

[0051] A method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material, the steps are as follows:

[0052] (1) Using brown corundum with a diameter of 2 mm as a sandblasting material, under 0.5 MPa of compressed air, the sandblasting nozzle is set 200 mm away from the titanium substrate, and the spray angle is about 25°, and the titanium substrate is sandblasted; then the titanium substrate is immersed in an oxalic acid aqueous solution with a mass concentration of 17% for 5 minutes for acid treatment to remove oxides, grease and other impurities on the surface of the substrate;

[0053] (2) immersing the treated titanium substrate in a hydrochloric acid solution with a mass concentration of 25%, acid etching at 80° C. for 15 min, then washing with water until neutral, and drying;

[0054] (3) dissolving ruthenium trichloride, iridium chloride, stannous chloride and nickel chloride in ethylene glycol to obtain a mixed metal salt solution; the mixed metal salt solution has a ruthenium concentration of 0.5 mg / mL; an iridium concentration of 0.5 mg / mL; a tin concentration of 0.3 mg / mL; and a nickel content of 0.2 mg / mL;

[0055] (4) uniformly coating the mixed metal salt solution on the acid-etched titanium substrate, heat-treating the coated titanium substrate, and then cooling it to room temperature, repeating the coating, heat-treating, and cooling steps 4 times to obtain a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material;

[0056] The heat treatment is to heat treat the coated titanium substrate at 120° C. for 1.5 hours and then at 450° C. for 30 minutes under an inert gas.

[0057] Embodiment 2-10

[0058] According to the method of Example 1, the tin (Sn) content of the mixed metal salt solution was changed. 2+ ) and nickel (Ni 2+ ) content, and heat treatment parameters, to prepare ruthenium, iridium, tin and cobalt mixed precious metal coating anode materials. The specific preparation parameters of Examples 1-10 are shown in Table 1.

[0059] Table 1 Preparation parameters

[0060]

[0061] Comparative Example 1

[0062] A method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material, the steps are as follows:

[0063] (1) The titanium substrate was immersed in an oxalic acid aqueous solution with a mass concentration of 17% for 5 minutes for acid treatment to remove oxides, grease and other impurities on the surface of the substrate;

[0064] Steps (2) to (4) are the same as in Example 1.

[0065] Comparative Example 2

[0066] A method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material, the steps are as follows:

[0067] Steps (1)-(2) are the same as in Example 1;

[0068] (3) replacing the solvent of the mixed metal salt solution with water;

[0069] (4) Same as Example 1.

[0070] Comparative Example 3

[0071] A ruthenium, iridium, tin, and nickel mixed precious metal coating anode material was prepared according to the method described in Example 1 of patent CN118241242B, except that cobalt was replaced by nickel and the nickel content (relative to tin) was set to 50 wt%.

[0072] The chlorine evolution potential of the electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 relative to the calomel electrode was tested in a saturated sodium chloride solution. The results are shown in Table 2.

[0073] Table 2 Chlorine evolution potential of samples

[0074] <![CDATA[2kA / m 2 ]]> <![CDATA[3kA / m 2 ]]> <![CDATA[4kA / m 2 ]]> <![CDATA[5kA / m 2 ]]> <![CDATA[6kA / m 2 ]]> <![CDATA[7kA / m 2 ]]> <![CDATA[8kA / m 2 ]]> Example 1 1.075 1.082 1.094 1.103 1.110 1.123 1.134 Example 2 1.092 1.101 1.114 1.122 1.134 1.142 1.152 Example 3 1.108 1.116 1.124 1.133 1.141 1.150 1.157 Example 4 1.064 1.071 1.082 1.094 1.1015 1.115 1.129 Example 5 1.104 1.112 1.123 1.131 1.139 1.148 1.155 Example 6 1.087 1.092 1.101 1.113 1.124 1.136 1.147 Example 7 1.079 1.085 1.093 1.102 1.114 1.125 1.136 Example 8 1.085 1.096 1.102 1.113 1.125 1.133 1.142 Example 9 1.067 1.078 1.085 1.096 1.105 1.119 1.128 Example 10 1.101 1.110 1.119 1.127 1.136 1.145 1.153 Comparative Example 1 1.112 1.133 1.152 1.175 1.182 1.208 1.223 Comparative Example 2 1.109 1.129 1.147 1.172 1.189 1.201 1.217 Comparative Example 3 1.081 1.092 1.101 1.114 1.125 1.139 1.154

[0075] The current efficiency and enhanced electrolysis life of the electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were measured, wherein the test temperature for the current efficiency (refer to the analysis method for the effective chlorine concentration in GB12176-90) was 10°C, the reference electrode was a saturated calomel electrode, and the applied current density was 0.5 A / m 2 The enhanced electrolysis life test was carried out in seawater at a temperature of 10°C and a current density of 5000A / m 2 The measurement results are shown in Table 3.

[0076] Table 3 Current efficiency and enhanced electrolysis life

[0077]

[0078]

[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material, characterized in that: The following steps are involved: (1) The titanium substrate is sandblasted and then acid treated to remove oxides, grease and other impurities on the surface of the substrate; (2) immersing the treated titanium substrate in an acid solution for acid etching, then washing with water until neutral, and drying; (3) preparing a mixed metal salt solution containing ruthenium, iridium, tin and nickel; (4) uniformly coating the mixed metal salt solution on the acid-etched titanium substrate, heat-treating the coated titanium substrate, and then cooling it to room temperature, repeating the coating, heat-treating, and cooling steps 3-4 times to obtain a ruthenium, iridium, tin, and cobalt mixed precious metal coating anode material; The heat treatment is to heat treat the coated titanium substrate at 100° C.-200° C. for 1 h-10 h under inert gas, and then heat treat it at 400° C.-600° C. for 20 min-240 min.

2. The method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material according to claim 1, characterized in that: The sandblasting material used in the sandblasting treatment in step (1) is steel shot or brown corundum.

3. The method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material according to claim 1, characterized in that: The acid treatment in step (1) is to immerse the titanium substrate after sandblasting in an oxalic acid aqueous solution with a mass concentration of 15%-20% for 5-10 minutes.

4. The method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material according to claim 1, characterized in that: The acid solution in step (2) is a hydrochloric acid solution or an acetic acid solution with a mass concentration of 20-30%.

5. The method for preparing anode material of ruthenium, iridium, tin and nickel mixed noble metal coating according to claim 1, characterized in that: The acid etching in step (2) is carried out at a temperature of 75 to 85° C. and for a time of 10 to 30 minutes.

6. The method for preparing a ruthenium, iridium, tin, and nickel mixed noble metal coating anode material according to claim 1, characterized in that: The mixed metal salt solution in step (3) is a mixed solution of a soluble ruthenium salt, a soluble iridium salt, a soluble tin salt, and a soluble nickel salt; the solvent of the mixed metal salt solution is any one or two of ethanol, ethylene glycol, n-butanol, or isopropanol.

7. The method for preparing anode material of ruthenium, iridium, tin and nickel mixed noble metal coating according to claim 1, characterized in that: The soluble ruthenium salt is any one or more of ruthenium nitrate, ruthenium trichloride, ruthenium sulfate, and ruthenium acetate; The soluble iridium salt is any one or more of iridium nitrate, iridium chloride and iridium sulfate; The soluble tin salt is any one or more of tin tetrachloride, stannous chloride and tin sulfate; The soluble nickel salt is any one or more of nickel acetate, nickel chloride, nickel sulfate and nickel nitrate.

8. The method for preparing anode material of ruthenium, iridium, tin and nickel mixed noble metal coating according to claim 1, characterized in that: In the mixed metal salt solution, the concentration of ruthenium is 0.3-0.6 mg / mL; the concentration of iridium is 0.3-0.6 mg / mL; the concentration of tin is 0.3-1 mg / mL; and the concentration of nickel is 0.2-0.8 mg / mL.

9. A ruthenium, iridium, tin, and nickel mixed precious metal coating anode material prepared according to the method of any one of claims 1 to 8.

Citation Information

Patent Citations

  • A coated titanium anode for circulating cooling water treatment, its preparation method and application

    CN113800606B

  • A ruthenium, iridium, tin and cobalt mixed precious metal coating anode material and preparation method thereof

    CN118241242B